IN VITRO ANTI-DIABETIC ACTIVITY PUNICA GRANATUM LINN LEAF EXTRACT - PALANISAMY, VAIJAYANTHIMALA; A, MUTHUMANIKANDAN; BALAKRISHNAN, SANGAMESWARAN (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: The present investigation deals with the study of in vitro anti-diabetic activity by inhibition of intestinal absorption of glucose by alpha-amylase method. Punica granatum L plant is a fruit-bearing deciduous shrub. It is used in the treatment of pneumonia as a bitter tonic also used in the treatment of flu, mouth and lip infection, antifungal, and immunosuppressant which used to treat heart disorders, stomach disorders, dental care, anemia, osteoarthritis, and anti-diabetic. The intestinal digestive enzymes such as alpha-glucosidase and alpha-amylase have played a vital role in carbohydrate digestion that these can be an important approach in managing of blood glucose. Methods: The air-dried powder of P. granatum Linn (leaf part) was extracted using a Soxhlet apparatus with ethanol extract of Psidium guajava (EEPG) and water aqueous extract of P. granatum (AEPG) as solvent. The extracts were concentrated under reduced pressure. The activities were carried out using the following concentration (10, 20, 30, 40, and 50 μg/mL) and compared with Acarbose as standard drug. It has significant in vitro anti-diabetic in alpha-amylase method. Results: The extract of P. granatum possessed significant anti-diabetic property in EEPG than compared to AEPG. Conclusion: Activity may be due to the presence of chemical profile such as glycosides, flavonoids, and terpenoids. The results of the study have suggested in the use of P. granatum Linn. as a potent anti-diabetic in several applications.